The Moderating Role of E-WOM on the Effects of Perceived Quality and Brand Ambassador on Purchase Decisions for Running Accessories: Study of Medan Polonia CFD Participants - Maximilian; Rusdiana Br Simamora; Feriani Astuti Br Tarigan (Penerbit Jurnal Indonesia, 2026)
The increasing popularity of running activities has influenced consumer behavior, particularly in purchasing sports accessories that support performance and lifestyle needs. Understanding factors affecting purchase decisions has become increasingly important as consumers are exposed to both product-related and promotional influences. This study aims to examine the effects of perceived quality and brand ambassadors on purchase decisions and investigate the moderating role of electronic word of mouth among active runners at Car Free Day Medan Polonia. Quantitative approach using purposive sampling was implemented, involving 100 active runners. Data were collected through questionnaires and analyzed using Moderated Regression Analysis (MRA). The findings conclude that perceived quality and brand ambassador had significant impact (partial and simultaneously) to purchase decision, but e-WOM still failed to demonstrate a significant moderating effect.